Synthesis, Characterization and Antimicrobial Screening of Some 3d-Metal Complexes of N and O Containing Schiff Bases - Rai, B.K.; Kumar, Bimal (Asian Journal of Chemistry, 2010)
Complexes of Co(II), Ni(II) and Cu(II) with 8,8-dimethyl-2,3,4, 5,7,8-hexahydro diazepino[2,1- b]benzothiazol-10(9H) semicarbazone [DHDBS] have been prepared and their characterization have been done by microanalytical data, IR, UV, molar conductance and magnetic measurements. On the basis of above physicochemical and spectroscopic measurements, it is proposed that the compound DHDBS behaves as a neutral bidentate ligand and coordination proposes through azomethine N and carbonyl oxygen atom of semicarbazone moiety. The remaining positions of metal ions are satisfied by negative ions, such as, Cl–, Br–, I– and NO3 –. Electronic spectral data and magnetic susceptibility measurement proposes octahedral geometry for the complexes. The complexes are also screened for their antimicrobial potential against selected bacteria and fungi.